Anti-Liver Fibrosis Activity and the Potential Mode of Action of Ruangan Granules: Integrated Network Pharmacology and Metabolomics - Shang, Xiaofei; Yuan, Huixin; Dai, Lixia; Liu, Yang; He, Jian; Chen, Huan; Li, Hongyan; Li, Xiuhui (Frontiers in Pharmacology, 2022)
Ruangan granules (RGGs) have been used to treat liver fibrosis with good clinical efficacy for many years. However, the potential mechanism of action of RGGs against liver fibrosis is still unclear. In this study, we evaluated the quality and safety of this preparation and aimed to explore the anti-liver fibrosis activity and potential mode of action of RGGs using network pharmacology and metabolomics. The results showed that RGGs contained abundant ferulic acid, salvianolic acid B and paeoniflorin, and at the given contents and doses, RGGs were safe and presented anti-liver fibrosis activity. They presented anti-liver fibrosis activity by improving liver function (ALT and AST, p<0.01) and pathology and decreasing fibrosis markers in the serum of rats caused by CCl4, including HA, LN, PC III, HYP, CoII-V, and α-SMA, and the oxidant stress and inflammatory response were also alleviated in a dose-dependent manner, especially for high-dose RGGs (p<0.01). Further studies showed that RGGs inhibited the activation of the PI3K-Akt signaling pathway in rats induced by CCl4, regulated pyrimidine metabolism, improved oxidative stress and the inflammatory response by regulating mitochondrial morphology, and alleviated liver fibrosis. Luteolin, quercetin, morin and kaempferol were active compounds and presented the cytotoxicity toward to LX-02 cells. This study provides an overall view of the mechanism underlying the action of RGGs protecting against liver fibrosis.